PLGA sustained-release microspheres loaded with an insoluble small-molecule drug: microfluidic-based preparation, optimization, characterization, and evaluation in vitro and in vivo. (31st December 2022) - Su, Yue; Liu, Jia; Tan, Songwen; Liu, Wenfang; Wang, Rongrong; Chen, Chuanpin
Abstract: Microspheres play an important role in controlling drug delivery and release rate accurately. To realize the sustainable release of insoluble small-molecule drugs, a new three-phase flow-focusing microfluidic device was developed to produce the drug-loaded sustained-release microspheres which were prepared with bicalutamide (BCS class-II) as the model drug and poly(lactide-co-glycolide) (PLGA) as the carrier material. Under optimized prescription conditions, the microspheres showed a smooth surface and uniform size of 51.33 μm with a CV value of 4.43%. Sustained-release microspheres had a releasing duration of around 40 days in vitro without any initial burst release. The drug release mechanism of the microspheres was drug diffusion and polymer erosion. Meanwhile, the drug release of microspheres in vivo could be up to 30 days. Briefly, the microfluidic device in this study provides a new solution for the preparation of sustained-release microspheres for insoluble small-molecule drugs. PLGA sustained-release microspheres developed by the microfluidic device have good application prospects in precise delivery and sustainable release of insoluble small-molecule drugs.